“There were Days when I Couldn’t Go On”: The Emotional Roller Coaster of the Practicum (Papeles, 2026)
Introduction: Practicum is one of the most transformative stages of teacher education; for many preservice teachers, it signifies a crucial transition from theory to practice. However, this transition involves mixed emotions influencing teacher identity and professional growth. Based on the hypothesis that emotions significantly affect teachers’ developmental trajectories, this narrative inquiry study examined the emotional triggers experienced by preservice English teachers during their practicum. Methodology: Data collection methods included semi-structured interviews, visual narratives, and journal entries over five months involving a sample of five participants. Data was analyzed using thematic coding. The study employed narrative analysis to scrutinize the documented emotional experiences. Results and Discussion: The findings demonstrated that the sources of emotions, such as happiness, pride, excitement, and gratitude, were instructional convergence, favorable student feedback, learning, engagement, participation, and behavior. Conversely, emotions like frustration, sadness, anxiety, fear, and stress were triggered by feelings of unpreparedness, disruptive student behavior, methodology to teach children, classroom management, instructional divergence, limited classroom interaction, and special needs students. Conclusions: Research implications underscore the importance of emotional support in teacher training programs, suggesting that understanding and addressing emotional triggers can enhance teacher preparation and resilience. This study highlights the influence of emotional experiences on shaping teachers' professional identities and pedagogical beliefs.
Keywords: preservice teachers